Digital Stress over the Life Span: The Effects of Communication Load and Internet Multitasking on Perceived Stress and Psychological Health Impairments in a German Probability Sample. - Reinecke, Leonard; Aufenanger, Stefan; Beutel, Manfred E.; Dreier, Michael; Quiring, Oliver; Stark, Birgit; Wölfling, Klaus; Müller, Kai W. (Media Psychology)
The present study investigated the psychological health effects and motivational origins of digital stress based on a representative survey of 1,557 German Internet users between 14 and 85 years of age. Communication load resulting from private e-mails and social media messages as well as Internet multitasking were positively related to perceived stress and had significant indirect effects on burnout, depression, and anxiety. Perceived social pressure and the fear of missing out on information and social interaction were key drivers of communication load and Internet multitasking. Age significantly moderated the health effects of digital stress as well as the motivational drivers of communication load and Internet multitasking. The results, thus, underline the need to address digital stress from a life span perspective.